2019
DOI: 10.1039/c9nj02976a
|View full text |Cite
|
Sign up to set email alerts
|

Design of nickel donor–acceptor dithiolenes for 2nd order nonlinear optics: an experimental and computational study

Abstract: This study, concerning the influence on the NLO properties of a remote functionality in the donor of D–Ni–A dithiolenes 1–4, allows to point out the relationship between NLO properties and the donor capability in modulating the low-energy absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Gem-dithiolates are comparatively less studied than related dithiocarboxylates [20][21][22][23]. There are some reports in the literature regarding their application as ligands for the preparation of complexes exhibiting non-linear optical activity as well as possessing extraordinary magnetic properties [24]. The simplest structures that were classified both as gem-dithiolate and dithiocarboxilate are trithiocarbonate salts.…”
Section: Resultsmentioning
confidence: 99%
“…Gem-dithiolates are comparatively less studied than related dithiocarboxylates [20][21][22][23]. There are some reports in the literature regarding their application as ligands for the preparation of complexes exhibiting non-linear optical activity as well as possessing extraordinary magnetic properties [24]. The simplest structures that were classified both as gem-dithiolate and dithiocarboxilate are trithiocarbonate salts.…”
Section: Resultsmentioning
confidence: 99%
“…showing the capability of the novel derivatives to respond to external stimuli (protons, silver ions, and light-irradiation) to obtain multifunctional linear and nonlinear chromophores will be presented [31][32][33][34][35]. Promising and less promising results in the production of 2 nd NLO-active materials where chromophores are embedded into polymeric PMMA (PolyMethylMethAcrylate) poled films or form crystals belonging to non-centrosymmetric point groups are also here shortly discussed.…”
Section: Chartmentioning
confidence: 99%
“…The same A2 Acceptor (R=Bz) has been employed to synthesize Ni-complexes [NiA2-Dn] (n = 3-6), on varying the Donor [33]. Despite, as said, the corresponding platinum-complexes would exhibit larger NLO responses, the use of nickel-metal offers advantages in terms of cost and depletion of precious metals and in terms of higher solubility of related complexes in common organic solvents.…”
Section: Inspection Of Table 2 Further Confirms That Inside the D-m-a...mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Both experimental and theoretical investigations showed that organometallic complexes possess low-lying charge-transfer transitions and fine-tuned NLO properties due to their diversity of ligands and the presence of a redox-active metal center. [16][17][18][19][20][21][22] Therefore, organometallic NLO materials must have more extensive applications compared to those pure inorganic or organic NLO materials. [23][24][25][26] Among various organometallic complexes, compounds containing transition metals, Ru(II), Ir(III), Os(II), Pt(II), Pd(II) or Zn(II), have attracted considerable attention due to their unique structural and high environmental stability.…”
Section: Introductionmentioning
confidence: 99%